Frauenfiguren in Heinrich Bölls Werken und ihre Rollen in der Erzählstruktur: zu Frauenfiguren in Heinrich Bölls Romanen Billiard um halb zehn, Ansichten eines Clowns, Gruppenbild mit Dame und Erzählung Die verlorene Ehre der Katharina Blum - Kristina Jokić (Acta Neophilologica, 2011)
The following article presents female characters and their role in four important novels by Heinrich Böll. The central female characters, who are the subject of this research, are Johanna Fähmel from the novel Billard um halb zehn (1959), Marie Derkum (Ansichten eines Clowns, 1963), Leni Pfeiffer, the heroine of the novel Gruppenbild mit Dame (1971) and Katharina Blum from the novel Die verlorene Ehre der Katharina Blum (1974). Heinrich Böll's novels were often studied and analysed. However, in those studies very little attention was devoted to female characters. At first sight, they appear to be of lesser importance; however, their role in the narrative structure should not be neglected. Although some literature researchers including Dorothee Römhild and Evelyn T. Beck were very critical of them and labelled them as dependent, traditional and completely subordinate to men, this article is trying to prove the opposite. Female characters in Heinrich Böll's novels are very complex, and the society tends to be ambivalent about them. Still, the most important fact is that they affect the narrative structure both directly and indirectly, thus representing an indispensable element in Böll's novels.